Analisa Hukum Terhadap Pengaturan Hak Guna Usaha di Ibu Kota Negara - Retno Ayuningtyas, Tri; Nisfu Laila Indah Septiana; Adellia Sallwa Baqa Rizki; Icmi Ag Rohmah; Made Sarmila (LPPM Universitas Ekasakti Padang, 2024)
Indonesia has a 2045 Golden Indonesia Vision, which is to become a “Sovereign, Advanced and Sustainable Archipelago”. To realize Indonesia's economic target 2045, the Government is moving the National Capital City (hereinafter referred to as IKN) as one of the strategies to realize Indonesia's economic target 2045, namely more inclusive and equitable economic growth through accelerated development of Eastern Indonesia. The relocation of the National Capital from Java Island to Kalimantan Island is one of the efforts to encourage regional equity so as to reduce the gap between Eastern Indonesia (KTI) and Western Indonesia (KBI), especially between the Java Region and outside the Java Region. IKN is one of the National Strategic Plans whose development is carried out in Sepaku, North Penajam Paser Regency. To build a new city, the government needs to have a strategy to attract investors both from within and outside the country. One of the business strategies that will be provided by the government is the granting of 2 (two) HGU cycles with a period of up to 190 years. The granting of such a long period of rights is not accompanied by arrangements to revoke/remove the rights that have been granted. This is considered contrary to the HGU arrangement in Law No. 5 of 1960 Basic Agrarian Principles Regulation